Cardiac damage in autoimmune diseases: Target organ involvement that cannot be ignored - Pan, Shu-Yue; Tian, Hui-Min; Zhu, Yong; Gu, Wei-Jie; Zou, Hao; Wu, Xu-Qiang; Cheng, Rui-Juan; Yang, Zhi (Frontiers in Immunology, 2022)
Autoimmune diseases are diseases that cause damage to the body’s own tissues as a result of immune dysfunction, often involving multiple organs and systems. The heart is one of the common target organs of autoimmune diseases. The whole structure of the heart can be affected, causing microcirculatory disorders, arrhythmias, pericardial damage, myocarditis, myocardial fibrosis, and impaired valvular function. However, early clinical manifestations of autoimmune heart damage are often overlooked because they are insidious or have no typical features. The damage is often severe and irreversible when symptoms are apparent, even life-threatening. Therefore, early detection and treatment of heart damage in autoimmune diseases is particularly important. Herein, we review the clinical features and mechanisms of cardiac damage in common rheumatic diseases.